Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - Vijay Prakash, K.; Geetha Vimala, Ch. S.; Preethi Latha, T.; Jayaram, Chiranjivi; Nagamani, P. V.; Laxmi, Ch. N. V. (Frontiers in Marine Science, 2021)
The COVID-19 has jeopardized the entire world and this pandemic has had a devastating impact on both lives and livelihoods in India. In order to defeat this mammoth wide spreading, the only way is to shut down the socio-economic activities and maintaining the minimal human interaction with LOCKDOWN. This lockdown has manifested in a pollution curtailment in almost all the spheres of the Planet and marine pollution is one amongst them. Quantifying this decrease in pollution levels enables the scientific community to assess the sole contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of stringent lockdown period (phase 1&2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, Kd(490) by using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48%, and 37.50% due to minimal vessel movement and cargo handling in Chennai and Ennore ports, respectively. The stringent lockdown led to the operation of fewer thermal plant units, emanated less amount of fly ash, resulted in 28.05% reduction in SPM levels over Ennore creek. As the industrial and commercial activities were subsided, the city’s water bodies are clearer than they were a fortnight ago, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in Kd(490) showed a positive relationship with SPM thus proved improved coastal water quality by the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and observed reduced levels in particulate matter concentration (PM2.5&PM10) for Adyar residential area (24.38% & 28.43%) and for Nungampakkam commercial area (36.09% & 67.18%). Significant reduction in PM2.5 concentration (45.63%) was observed at Ennore-Manali Industrial region.